The Government’s Role in Decreasing Divorce Rates in Indonesia: The Case of Aceh and South Sulawesi - Mursyid Djawas; Ridhwan Ridhwan; Soraya Devy; Asmaul Husna (Universitas Islam Negeri Jakarta, 2021)
This study discusses the increase in divorce rates in Indonesia, especially in Aceh and South Sulawesi. This study investigates factors affecting the increase of divorce rates and the role of the government in decreasing the divorce rates. This research is an empirical legal study that used structural functionalism theory and role theory. Data was collected through questionnaires, interviews, and document studies. This study concludes that the factors that influence the increase in divorce rates in Indonesia, especially in Aceh and South Sulawesi, are economy, education, the lack of religious understanding, social media, early marriage, and the lack of empathy on the rights and obligations of husband/wife. As a result, the high divorce rate in Indonesia negatively affects children, families and the nation. The government's efforts to address this reality are by holding out pre-marital courses, preaching marriage sermons to strengthen family and prevent a divorce, holding happy family contests, and designing a marriage guidance module for brides and grooms. These efforts, in the sociology of law context, are the government's function and role in anticipating the increasing divorce rates so the social system stability can be maintained. Abstrak:Penelitian ini membahas upaya pemerintah dalam menurunkan angka perceraian di Indonesia khususnya di Aceh dan Sulawesi Selatan. Studi ini mengkaji faktor-faktor yang mempengaruhi tingginya perceraian dan dampak yang disebabkannya. Sumber data dalam penelitian hukum empiris ini adalah kuisioner, wawancara, dan studi dokumen. Data-data tersebut kemudian diolah menggunakan teori fungsionalisme struktural dan teori peran. Temuan dalam penelitian menjelaskan bahwa penyebab meningkatkan perceraian di Aceh dan Sulawesi Selatan adalah ekonomi, pendidikan, kurangnya pemahaman agama, media sosial, pernikahan dini, dan kurangnya empati terhadap kewajiban suami/istri. Tingginya perceraian ini berdampak negatif kepada anak, keluarga, dan bangsa. Upaya pemerintah untuk mengatasi kenyataan ini adalah dengan mengadakan kursus pranikah, khotbah nikah untuk memperkuat keluarga dan mencegah perceraian, mengadakan kontes keluarga bahagia, dan merancang modul panduan pernikahan untuk calon pengantin. Upaya-upaya tersebut, dalam konteks sosiologi hukum, merupakan fungsi dan peran pemerintah dalam menjaga stabilitas sistem sosial.